Warm underwater water-jet massage improves recovery from intense physical exercise - Viitasalo, J. T.; Niemela, K.; Kaappola, R.; Korjus, T.; Levola, M.; Mononen, H. V.; Rusko, H. K.; Takala, T. E. (European Journal of Applied Physiology, 1995)
Junior track and field athletes (N = 14) engaged in randomized week-long training of five strength/power sessions. One week used underwater water-jet massage treatments three times for 20 min during the treatment week. During the treatment week continuous jumping power and ground contact time improved. In the control week serum myoglobin increased. It was suggested that underwater water-jet massage in connection with intense strength/power training increases the release of proteins from muscle tissue into the blood and enhances the maintenance of neuromuscular performance capacity. Implication: Water-jet massage could assist in recovery from intense strength/power training.